2007
DOI: 10.1016/j.bbamem.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Phase studies of model biomembranes: Complex behavior of DSPC/DOPC/Cholesterol

Abstract: We have undertaken a series of experiments to examine the behavior of individual components of cell membranes. Here we report an initial stage of these experiments, in which the properties of a chemically simple lipid mixture are carefully mapped onto a phase diagram. Four different experimental methods were used to establish the phase behavior of the 3-component mixture DSPC/DOPC/chol: (1) confocal fluorescence microscopy observation of giant unilamellar vesicles, GUVs; (2) FRET from perylene to C20:0-DiI; (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
282
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(305 citation statements)
references
References 45 publications
22
282
0
1
Order By: Relevance
“…7 ; Tables 2, 3 ). Considering the phase diagrams of ternary mixture ( 39,41,(43)(44)(45), a suffi cient degree of ergosterol depletion would cause the transition from the L o phase to the L ␤ phase. The ergosterol content in the sur2 ⌬ csg1 ⌬ csh1 ⌬ mutant was decreased by ‫ف‬ 20-30% relative to WT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ; Tables 2, 3 ). Considering the phase diagrams of ternary mixture ( 39,41,(43)(44)(45), a suffi cient degree of ergosterol depletion would cause the transition from the L o phase to the L ␤ phase. The ergosterol content in the sur2 ⌬ csg1 ⌬ csh1 ⌬ mutant was decreased by ‫ف‬ 20-30% relative to WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the extension of both the hydrophilic head group and the C4-OH are necessary for effective growth in limited nutrient conditions. Studies of model membranes show that liquid-disordered (L d ) and liquid-ordered (L o ) phases coexist in ternary mixtures of sterol (e.g., ergosterol), sphingolipids, and glycerolipids (e.g., dipalmitoylphosphatidylcholine) (37)(38)(39)(40)(41). While the L d phase is a fl uid state, the L o phase is an intermediate state between gel and liquid crystal phases, characterized by tight packing and rapid lateral diffusion .…”
Section: The Lateral Diffusion Of Tat1-egfp and Hxt1-egfp Is Affectedmentioning
confidence: 99%
“…The disc-shaped region around the vertex with initial area A(v i ) is projected out a distance ∆R along the normals of the edges, as shown in figure 4. Let the two faces g (1) ij and g (2) ij be defined by the three points,…”
Section: B Discrete Line Tensionmentioning
confidence: 99%
“…The three component lipid system, distearoyl-phosphatidylcholine (DSPC)/dioleoylphosphatidylcholine (DOPC)/cholesterol (CHOL) has a well characterized phase diagram, with a region of liquidliquid (L o + L d ) coexistence that is readily observable in giant unilamellar vesicle (GUV) studies as large round domains [1,2]. This mixture is a useful model for understanding the general nature of bilayers containing a high melting lipid (DSPC), a low melting lipid (DOPC), and cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we prepared model membrane vesicles composed of various combinations of B. burgdorferi lipids. Model membrane vesicles have proven to be very useful systems for defining the abilities of lipids to form ordered domains in membranes and identifying conditions in which such domains exist as nanoscale-size domains (38)(39)(40)(41)(42)(43)(44)(45). Using model membrane vesicles, we found that the major Borrelia lipids differ greatly in their ability to support ordered-domain/raft formation.…”
Section: Introductionmentioning
confidence: 95%